ADAPTAÇÕES ORGANIZACIONAIS ESTIMULADAS PELA NORMA DE DESEMPENHO NAS CONSTRUTORAS BRASILEIRAS - Santos, Paulo Ricardo Ramos; Santos, Débora de Gois (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
The performance standard, NBR 15.575, constitutes a divisive landmark in Brazilian civil construction by introducing the concept of performance in an environment with prescriptive standards. From the beginning of its validity there was an expectation of improvement of the housing constructions coming from the maturity of the challenges imposed by it. In this way, construction companies need to structure themselves in organizational terms to ensure compliance with such regulations. Given this context, the present research proposed to investigate the organizational changes promoted by the builders to adapt to NBR 15.575. The research was carried out from a multiple case study, with descriptive features. The data were collected from structured interviews with representatives of 16 construction companies from a capital of a state in the Northeast. The results show that the performance standard stimulates, besides a technical quality improvement framework, a better structuring of the activity flow and alignment of the internal processes of the companies with the new requirements of the sector.